PENGARUH RUTE SINTESIS TERHADAP KEEFEKTIFAN PENGIKATAN GUGUS PDETA PADA SINTESIS Fe3O4@SiO2@PDETA - Susanto Susanto; Ricka Prasdiantika (Universitas Gadjah Mada, 2018)
Synthesis of Fe3O4@SiO2 modified with propyldiethylenetriamine (Fe3O4@SiO2@PDETA) with variation of synthesis routes have been investigated. Research was begun with synthesis of Fe3O4 using dispersion agent of trisodium citrate at coprecipitation system through stirring using ultrasonic wave. Coating magnetite with propyldiethylenetriamine modified silica was carried out through sol-gel process with two different mixing sequences of raw materials (two synthesis routes) with main materials of Fe3O4 synthesized, N-[3-(Trimethoxysilyl)propyl]-diethylenetriamine (TMSPDETA) and Na2SiO3. The products were characterized by fourier transform infrared (FTIR) spectrophotometer and scanning electron microscope-energy dispersive X-ray (SEM-EDX). Results indicate that Fe3O4@SiO2@PDETA has been synthesized succesfully. Fe3O4@SiO2@PDETA synthesized through route 1 (magnetite mixed with a mixture TMSPDETA and Na2SiO3) contains more propyldiethylenetriamine group than that of through route 2 (magnetite mixed with Na2SiO3 solution, then mixed with TMSPDETA)